The Face and the Divine Space - Pagh, Christian (Peripeti, 2017)
jesus_c_ odd _size (2000) is both a performance and an exhibition. The basic concept is a series of tableaux that takes place in different rooms, while the audience perambulates. As a spectator you walk about for more than 3 hours in a position where you have to relate to what is taking place around you.